Analysis of genetic parameters in creole cowpea (Vigna unguiculata (L.) Walp.) cultivars for green grain production (Research, Society and Development, 2025)
Creole cowpea varieties exhibit broad genetic variability and represent valuable resources for participatory breeding programs. This study aimed to analyze genetic parameters and estimate correlations among morpho-agronomic traits in creole cowpea genotypes grown for green grain production from the germplasm bank of IFPE – Vitória de Santo Antão. Ten genotypes obtained from the IFPE germplasm bank and rural communities in Itaquitinga and Goiana, Pernambuco, were evaluated. The experiment was conducted in a randomized block design with four replications, using plots composed of 2 m rows spaced 0.80 m between rows and 0.40 m between plants. Twenty quantitative traits were measured following descriptors adapted from Bioversity International. Data were subjected to analysis of variance, Scott–Knott test (p